FAKTOR RISIKO PENYAKIT DEGENERATIF PADA USIA LANJUT SEDENTER: STUDI KASUS PADA PEREMPUAN USIA LANJUT DI PANTI WREDA KHUSNUL KHOTIMAH, TANGERANG - Mukhtar, Diniwati (Lembaga Penelitian Universitas YARSI, 2007)
Prevalence of degenerative diseases in the elderly is currently increasing worldwide due to several factors, such as structural and metabolic distortion, gender and physical activity. In Indonesia, as the life expectancy of the people tend to extend, the proportion of the elderly also increases over time, with various consequences. The present study aims to determine the risk for degenerative diseases among the elderly women residing in a nursing home in Tangerang District, Banten Province, Indonesia. The study was conducted using a descriptive case study design, involving anthropometric as well as blood examinations of the subject, and questionnaire pertaining age and family status, educational background and the length of stay in the nursing home. Results indicated that the mean of age of the subjects was 70 ± 6.4 years. The anthropometric measurement demonstrated a high prevalence of subjects with waist-to hip ratio of 0,89 ± 0,04 although the BMI risk was only noted in 45% of the subjects. The blood chemistry analysis indicated that the majority of the subjects had a high total cholesterol and low HDL cholesterol blood level, whereas the other components were relatively normal. The findings indicated that the reduced physical activity may contribute to the atherosclerosis risk factor as well as other degenerative diseases.